Addition
 
3 + 2 = 12 + 4 = 1 + 12 = 3 + 5 =
1 + 1 = 11 + 7 = 1 + 7 = 10 + 0 =
9 + 0 = 10 + 11 = 4 + 1 = 0 + 12 =
3 + 3 = 8 + 1 = 7 + 9 = 8 + 10 =
11 + 2 = 7 + 8 = 10 + 0 = 11 + 6 =
9 + 1 = 6 + 11 = 10 + 7 = 2 + 4 =
4 + 4 = 5 + 1 = 0 + 1 = 9 + 12 =
12 + 3 = 4 + 5 = 3 + 9 = 0 + 11 =
7 + 2 = 3 + 8 = 2 + 3 = 7 + 9 =
2 + 5 = 2 + 11 = 5 + 11 = 10 + 4 =
0 + 4 = 1 + 2 = 8 + 2 = 5 + 3 =
8 + 7 = 0 + 5 = 11 + 9 = 8 + 11 =
2 + 6 = 11 + 8 = 11 + 4 = 2 + 10 =
10 + 5 = 10 + 12 = 1 + 11 = 6 + 8 =
8 + 8 = 9 + 2 = 4 + 6 = 0 + 3 =
3 + 7 = 8 + 9 = 7 + 0 = 4 + 2 =
11 + 6 = 7 + 12 = 6 + 7 = 11 + 10 =
6 + 9 = 2 + 2 = 9 + 11 = 2 + 9 =
0 + 8 = 1 + 6 = 12 + 6 = 9 + 7 =
12 + 8 = 0 + 9 = 12 + 0 = 12 + 2 =
6 + 10 = 12 + 12 = 2 + 8 = 6 + 1 =
1 + 9 = 11 + 3 = 5 + 2 = 10 + 9 =
9 + 9 = 10 + 6 = 8 + 10 = 1 + 7 =
7 + 11 = 9 + 9 = 7 + 1 = 8 + 3 =
2 + 11 = 8 + 0 = 10 + 8 = 12 + 1 =